Effect of liming and fertilization on nutritional state and dry rubber production of rubber-tree - Filho, Adonias de Castro Virgens; Moreira, Adônis; Castro, Paulo Roberto de Camargo e (Pesquisa Agropecuaria Brasileira, 2001)
The effects of lime and NPK application on nutritional state and dry rubber production of clone RRIM 600 were evaluated. The experimental design was a randomized split-plot with four replicates. In the plots were tested two controls (without fertilizer and without lime; without fertilizer and with lime) and six treatments with lime and NPK fertilization (N1P1K0, N2P2K0, N1P1K1, N2P2K1, N1P1K2 and N2P2K2). The two sub-treatments were the following tapping systems: ½S d/4 6 d/7 ET 2.5% LaPa 1/1 10/y (S1) and ½S d/6 6 d/7 ET 5.0% LaPa 1/1 10/y (S2). The NPK levels used, in kg ha-1 y-1, were represented by 40 and 80 of N; 17.5 and 35.0 of P2O5 and 0, 33.2 and 66.4 of K2O. There was a significant effect of treatments on the N, P, S, Cu and Zn content in leaves. The N applied to soil up to the second dosage was not enough to increase the N level in leaves. Increasing the application of K2O, in the presence of N2P2, promoted a linear decreasing effect on the Zn level. The highest rubber yield (1,778.9 kg ha-1), as an average of the three years, was obtained with the treatment N2P2K1 plus liming, under both tapping systems.